United Kingdom : 2018 Article IV Consultation-Press Release; Staff Report; Staff Statement; and Statement by the Executive Director for United Kingdom. (IMF Staff Country Reports; Country Report ;, 2018)
The United Kingdom is set to exit the European Union in March 2019. It is now in the process of negotiating its withdrawal from the EU. Once an agreement is reached, there will be an implementation period through the end of 2020. Complex issues still remain to be resolved, including the future status of the land border with Ireland. Growth over the past year has been moderate. The post-referendum depreciation caused an increase in inflation, depressing private consumption. Business investment growth has been constrained by protracted uncertainty about the future trade regime and potential increases in trading costs. Nonetheless, slack in the economy is limited as weaker demand is matched by slower supply growth. Growth is expected to continue at a moderate pace, conditional on a smooth Brexit transition and some recovery in labor productivity. A key downside risk is an exit.